Studi Penerapan Intelligent Transportation System(ITS) Di Kabupaten Seram Bagian Barat - Hanok Mandaku; Marcus Tukan (Industrial Engineering Study Program, Pattimura University, 2010)
Transportation is a business transfer of cargo from point of origin to the point of destination with a conveyance or modes. In practice, transportation rarely use only one mode. The goal is to improve the effectiveness and efficiency of transport services. Because it involves more than one mode, then the exchange of information between the modes become very crucial point which is generally a weak implementation of a reliable transport and highly capable. West Seram regency (SBB) today has become